2016
DOI: 10.3106/041.041.0201
|View full text |Cite
|
Sign up to set email alerts
|

Primate Survey in a Bornean Flooded Forest: Evaluation of Best Approach and Best Timing

Abstract: Accurate determination of the abundance and distribution of animals, particularly endangered species, is a fundamental requirement for understanding their ecology and has important applications for their conservation. In Bornean flooded forests, various approaches have previously been used to conduct primate census, including foot-based land surveys and boat-based river surveys at different times of the day such as in the early morning and/or late afternoon. However, the accuracy of primate encounter frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 17 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…The population size of the proboscis monkey in the Lower Kinabatangan was higher in 2014 (1,960 individuals) than in 2004 (1,340 individuals). This difference could be a result of differences in data collection; the number of monkeys counted during late afternoon surveys could be three times more than counts of the same groups in the morning (Matsuda et al, 2016), which means the increased number of monkeys counted in 2014 may not be a sign of an actual increase in population size. River surveys in the three long-term monitoring sites suggested that these populations were stable.…”
Section: Discussionmentioning
confidence: 99%
“…The population size of the proboscis monkey in the Lower Kinabatangan was higher in 2014 (1,960 individuals) than in 2004 (1,340 individuals). This difference could be a result of differences in data collection; the number of monkeys counted during late afternoon surveys could be three times more than counts of the same groups in the morning (Matsuda et al, 2016), which means the increased number of monkeys counted in 2014 may not be a sign of an actual increase in population size. River surveys in the three long-term monitoring sites suggested that these populations were stable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, frequent recurrence at the same locations may facilitate accumulation of infective parasite stages and could result in reinfection ( Hausfater and Meade, 1982 ). Proboscis monkey groups return to sleeping sites ( Matsuda et al., 2016 ) and the surroundings of single trees appeared to be particularly popular as they were occupied regularly. The physical structure and location of both sleeping trees and their surrounding vegetation are important for the sleeping site selection of N. larvatus ( Thiry et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We independently walked each transect at a speed of ~ 1.5 km/hour (Peres, ) during daylight hours, pausing every 100m for 2 minutes to thoroughly search the area for primates (Pruetz & Leasor, ). Although transects were sampled between 0530–1730, most sampling took place between 0730–1145 and 1230–1600, meaning that groups were no longer in their sleeping trees yet any change in monkey detectability based on time of day would be accounted for given the broad spectrum of sampling times (Matsuda, Otani, Bernard, Wong, & Tuuga, ). To avoid the likelihood of repeated sampling of the same primate individuals and groups on the same day, adjacent transects were not sampled on the same day (i.e., only odd or even‐numbered transects were sampled on a given day to ensure that all transects sampled during a single day were separated by at least 300m) and individual transects were sampled a maximum of once daily, with one to three transects sampled concurrently in randomized order at any given time.…”
Section: Methodsmentioning
confidence: 99%